(untitled) (Mustansiria Dental Journal, 2024)
Aim of the study: The main goal of this study was to evaluate using of right-angle technique for detecting the impacted objects in maxilla and mandible arches in three dimensional radiographs. Material and Methods: eighteen patients, seventeen were males, with one female age ranging from eighteen to twenty-four years (according to patients who attend to oral radiology dental clinic). The two radiographs are taken at the right angle to each other. This will indicate the tooth’s position in the superior-inferior and anteroposterior relationships. Another radiograph was taken in true occlusal (cross-section) projection using an occlusal/periapical film will show the buccal (labial)- lingual and anteroposterior relationship. Results: the contrast value for the radiographs, in this case, is the following number which is ≤ 0.5. It was significant it means acceptable from a statistics point of view, which the numbering is ≥ 0.5 it was non-significant which means most cases are highly significant from in statistic point of view. Conclusion: according to values of outcomes and their significance can be used to the patient effectively detect this kind of impaction. Right angle technique is an effective to detect third dimension of impacted tooth (the depth) if it is buccally, lingually, mesially, distally or transverse. According to outcomes and its significance can be used to the patient effectively detect this kind of impaction.